ANALISIS PELUANG, MODAL DAN PENDAPATAN PADA USAHA JUICE GAUL DI KOTA SERANG - Ade Rahmat Hidayatulloh; Siti Fatonah; Tia Fitria Saumi (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The purpose of this study was to determine the opportunities, capital and income of the slang juice business in the city of Serang. This study aims to find out the opportunities that are used as a reference to get the idea of ​​opening juice slang, to get the first capital and develop a juice slang business in the city of Serang, the amount of daily and monthly income for slang juice, the number of juice slang outlets spread across the city and district. This research method uses qualitative research methods with data collection techniques using observation, interviews and documentation techniques. Then presented descriptively. The analysis used is a SWOT analysis to formulate a strategy based on logic that can maximize strengths and opportunities but simultaneously minimize weaknesses and threats. The results showed that based on the results of the SWOT strategy to develop a slang juice business, maintaining and improving product quality, maintaining selling prices, and creating product innovations, then the material capital collected came from personal savings, asset sales and bank loans. which increased significantly from 2016 to 2020